THE NEW MODEL OF ISRAELI SCHOOL BASED MANAGEMENT(SBM) IN 2012- THE SALVATION STEP FOR THE EDUCATION SYSTEM IMPROVEMEMT - Levnawi, Ayed Yousof (My University, 2016)
The Ministry of Israeli Education promoted elementary schools forward School Based Management (SBM) Reform, from viewpoint, which was supported by many researches in the world. SBM created several benefits, but new difficulties were encountered with the other two pieces of the trio - the Ministry of Education and local Authority.